A higher energy‐adjusted Dietary Inflammatory Index is positively associated with total and visceral body fat in young male adults. Issue 6 (17th April 2022) - Corrêa, Cinthia R.; da Costa, Bruno G. G.; Silva, Kelly S.; Shivappa, Nitin; Wirth, Michael D.; Hébert, James R.; Nunes, Everson A.
Abstract: Background: The energy‐adjusted Dietary Inflammatory Index (E‐DII™) has been associated with a high body mass index and markers of chronic diseases. Also, pro‐inflammatory diets with a high E‐DII have been positively associated with metabolic disturbances such as glucose intolerance and type II diabetes mellitus. However, it is unclear whether E‐DII scores are positively associated with body fat percentage and visceral fat per se . This cross‐sectional study aimed to evaluate whether the E‐DII is associated with body fat content and metabolic health indicators in lean and obese young men. Methods: The present study was conducted on 59 participants, without comorbidities, not using tobacco, medication and nutritional supplements. Dietary data were obtained by 3‐day food records to calculate E‐DII scores based on 28 food parameters. Body composition was assessed by dual X‐ray absorptiometry (DXA). Blood samples were taken to measure fasting glucose, insulin, triacylglycerols, total cholesterol, and low‐ and high‐density lipoprotein cholesterol. An oral glucose tolerance test also was performed. Associations were determined by mixed‐effects linear regression. Results: E‐DII scores ranged from −3.48 to +3.10. Energy intake was similar across E‐DII tertiles. After adjusting for covariates, the highest E‐DII tertile was associated with increased body fat, visceral adipose tissue and waist circumference. There was no association between E‐DII scores and glycaemic parameters. Conclusions: In young participants, a dietary pattern with a higher E‐DII (i.e., pro‐inflammatory) score was associated with high body fat and markers of central adiposity assessed by DXA, regardless of body mass. Key points: 1. Diet quality has been one of the hot topics investigated when looking into chronic disease prevention and treatment. 2. A common feature of chronic diseases is low‐grade chronic inflammation, which is associated with dietary habits and body fat. 3. The energy‐adjusted Dietary Inflammatory Index (E‐DII) is a tool for evaluating the inflammatory potential of a diet and it is not completely known whether E‐DII is associated with body adiposity or markers of metabolic health in healthy subjects. 4. The present study aimed to find potential associations between E‐DII, body fat and metabolic health in young healthy males. 5. The highest E‐DII tertile (towards pro‐inflammatory) was positively associated with increased body fat, visceral adipose tissue mass and waist circumference, regardless of body mass. 6. Following a diet with a pro‐inflammatory profile (higher E‐DII) is likely a contributor to the whole body and central obesity, with potential repercussions to future metabolic health. Abstract : Diets tending to be more pro‐inflammatory (higher Dietary Inflammatory Index [DII] scores) were positively associated with more body fat, independent of body weight. Diets with higher DII scores were positively associated with more visceral adipose tissue.